Harnessing oncolytic virus-mediated immunity - Volker Schirrmacher (Frontiers Research Topics, 2015)
Oncolytic viruses (OVs) have emerged as a promising anticancer treatment. OVs selectively infect, replicate in, and kill tumor cells. Oncolytic viral therapy occurs in two phases: an initial phase where the virus mediates direct oncolysis of tumor cells, and a second phase where an induced post-oncolytic immune response continues to mediate tumor destruction and retards progression of the disease. For a long time, the therapeutic efficacy was thought to depend mainly on the direct viral oncolysis based on their tumor selective replication and killing activities. But the post-oncolytic anti-tumor activity induced by the OV therapy is also a key factor for an efficient therapeutic activity. The topic adresses various strategies how to optimize OVs anti-tumor activity.